2015
DOI: 10.1039/c5ra13096d
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the aggregation of sodium dodecylsulphate in aqueous poly(ethylene glycol) solutions

Abstract: The role of PEG's of different molecular weights on the self-assembly of SDS and the role of added NaCl has been addressed opening new scopes for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…There is no interaction observed between PEG-400 and SDS in the bulk solution. The results are in a good agreement with previous findings (da Silva et al 2004;Dey et al 2015). Using isothermal titration calorimetry (ITC), Dai and Tam (2001) found that the binding behaviour of PEG and SDS in the bulk solution is dependent on the molecular weights of PEG.…”
Section: Surface and Interfacial Tensionssupporting
confidence: 91%
See 4 more Smart Citations
“…There is no interaction observed between PEG-400 and SDS in the bulk solution. The results are in a good agreement with previous findings (da Silva et al 2004;Dey et al 2015). Using isothermal titration calorimetry (ITC), Dai and Tam (2001) found that the binding behaviour of PEG and SDS in the bulk solution is dependent on the molecular weights of PEG.…”
Section: Surface and Interfacial Tensionssupporting
confidence: 91%
“…1, 2, 3, 4 and 5. Surface tension results follow the same trend as previous findings (Cooke et al 1998;Jones 1967;Müller et al 2003;Purcell et al 1998;Umlong and Ismail 2007); however, the previous minimum point, attributed to an SDS impurity (Dey et al 2015;Lin et al 1999;Umlong and Ismail 2007), has not been observed in surface tension measurements. Figure 1 shows that CAC occurs at the SDS concentration of 0.168 g/100 mL (0.7 CMC of free polymer solution).…”
Section: Surface and Interfacial Tensionssupporting
confidence: 88%
See 3 more Smart Citations